Pengaruh Pemilihan Metode Akuntansi Atas Biaya Research and Development (R&D) Terhadap Price Earnings Ratio (Studi Empirik Pada Perusahaan Sektor Industri Periode 2002-2005) - Michell Suharli; Ani Arisandi (Bina Nusantara University, 2009)
Earnings reflect the equity growth stemmed from various economic transaction, except shareholders’ transactions in certain periods. Similar to the net income concept, earnings concept includes all transactions in net revenue in current period. The research sample is 14 listed companies that reported Research & Development (R&D) expenses during 2002-2004 period. Research variables used are earnings (as the dependent variable) that is proxied by price earning ratio (PER), and accounting method chosen to record the R&D expenses (as the independent variable). The research model is a simple regression model. The result shows that accounting method chosen is significantly related to the PER, however appears does not influence the profit of the company.